Dental erosion in 12-year-old schoolchildren: a crosssectional study in Southern Brazil - K. G. PERES, M. F. ARMÃƒÆ’Ã…Â NIO, M. A. PERES, J. TRAEBERT, & J. T. DE LACERDA (Paediatric Dentistry, 2005)
The aim of this study was to assess the prevalence and severity of dental erosion among 12-year-old schoolchildren in Joaçaba, southern Brazil, and to compare prevalence between boys and girls, and between public and private school students.